Analysis of the Agricultural Drought Causes in Babylon Province - Talib , Zubaida Rifaat; Laffta , Suaad Jaber (Iraqi Journal of Science, 2024)
Drought is one of the challenges Iraq faced during this period, and the negative environmental effects that are apparent due to climate change have become essential topics that attracted the attention of urban planners. As the lack of rain and high temperatures are among the reasons for the drought increase, especially in desert areas, the Babil governorate was chosen as one of the governorates that suffered from agricultural drought. Agricultural drought indices were analyzed and monitored by downloading satellite images from the United States website for the period 1995-2021, where the area of ​​the Babylon governorate was 5119 . It was used to calculate agricultural drought for 1999-2015-2021; climatic elements data (temperature and precipitation) were taken for the same period. As it was found that the Babil governorate suffers from severe agricultural drought; in 2021 amounted to an area of 1982 , 32% due to a decrease in the rain and a rise in temperatures by 2 degrees compared to the general average, while the agricultural area amounted to 1263 , 27%, which is the highest rate recorded in 1999.